Central Exams Improve Educational Performance: International Evidence - Ludger Wößmann (Institut für Weltwirtschaft (IfW), 2002)
International comparative studies of student performance have initiated political discussions in countries all over the world on how to improve the educational achievement of students. The empirical evidence suggests that central exams help to achieve higher student performance. Central exams direct the incentives of all educational actors towards furthering students' knowledge. By providing the education system with performance information they improve the monitoring of students, teachers, schools, administrators, and parents. Using an international micro database of nearly half a million students, this paper finds that students in countries with central exitexam systems perform substantially better in their middle-school years in both math and science than students in countries without central exams. In quantitative terms, their advantage is 35 to 47 percent of an international standard deviation in test scores, or roughly the equivalent of one year of schooling. The beneficial effect increases as students advance through middle school. Good and bad students alike perform better in central-exam systems. In math, the gain of high-performing students is slightly larger than that of low-performing students. There is some evidence that central-exam systems equalize educational opportunities for students from different parental backgrounds. School autonomy in budgetary and salary decisions is detrimental in systems without central exams but turns around to be beneficial in systems with central exams. Thus, central exams seem to be a prerequisite for a decentralized system of autonomous schools to achieve high performance. The efforts of teachers and students are more concentrated on the goals of the education system when central exams are in place, and parental involvement becomes more informed and effective. Thus, central exams exert their effects through several different impact channels by changing the behavior of different actors in the education process. Given the shortcomings of most school- and teacherbased accountability systems and the substantially higher costs of most resource-based policies, central-exam systems seem a highly attractive policy alternative.
Keywords: 330; Bildungsniveau; Allgemeinbildende Schule; Leistungskontrolle; Agency Theory; Schätzung; Welt; Zentralexamen; Zentralabitur